Soft Skills and Self-Efficacy as Predictors of Employee Productivity - Risman; Sundari Rahman; Jumardi; Fitri (LPPM STIEM BONGAYA, 2026)
Employee productivity is a strategic factor that determines organizational competitiveness, particularly amid digital transformation and the evolving demands of the modern labor market. This study aims to examine the influence of soft skills and self-efficacy on employee productivity at PT Megahputra Sejahtera. Soft skills refer to non-technical abilities related to communication, collaboration, adaptability, and problem-solving, while self-efficacy reflects an individual’s belief in their capability to accomplish tasks effectively. Using a quantitative approach, data were collected from 30 employees selected through purposive sampling. Data analysis included validity testing, reliability testing, and multiple regression to assess both partial and simultaneous effects. The findings indicate that soft skills and self-efficacy have a positive and significant influence on employee productivity. These results highlight that strengthening interpersonal competencies and work-related confidence not only enhances individual effectiveness but also contributes directly to organizational performance outcomes. The study recommends that the company implement structured soft-skills training programs and self-efficacy enhancement interventions through coaching and systematic feedback.